THE NERVOUS ENVIRONMENT OF INDIVIDUAL SMOOTH MUSCLE CELLS OF THE GUINEA PIG VAS DEFERENS - Merrillees, Neil C. R. (The Rockefeller University Press, 1968)
Smooth muscle cells of the external longitudinal coat of the guinea pig vas deferens were followed for 480 µ at 4.5-µ intervals. Muscle bundles and fibers interwove, facilitating intermuscular and neuromuscular contacts. The ribbon- or rodlike muscle cells were about 450 µ long, 3,000 µ(3) in volume, and 4,500 µ(2) in area. The thickened nuclear zone lay anywhere along the middle one-third of the cell. Intercellular distances were 500–800 A. Intrusions were rare, and tight-junctions absent. At any level in a field of 80 muscle fibers there were 10–15 nerve bundles, each containing several varicose axons. Bundles and axons divided. Axons, en passage, were frequently within 500–1,000 A of a muscle fiber. En passage close contacts were rate. Axon terminations were bare, and bare axons invariably terminated. Bare terminations had scattered vesicle-laden varicosities and were from 10µ-60 µ in length, and all ended within 500 A of muscle fibers. Some made close contact with muscle fibers. Less than half of the muscle cells received this close contact, but some cells were approached by more than one termination. Most terminations involved more than one cell. Some cells had little or no innervation. Some groups of cells had a rich innervation. There was very little evidence of sensory innervation. These conclusions are not valid for other smooth muscles.